Synthesis and reactivity of NHC-coordinated phosphinidene oxide. Issue 75 (26th August 2021) - Dhara, Debabrata; Pal, Pradeep Kumar; Dolai, Ramapada; Chrysochos, Nicolas; Rawat, Hemant; Elvers, Benedict J.; Krummenacher, Ivo; Braunschweig, Holger; Schulzke, Carola; Chandrasekhar, Vadapalli; Priyakumar, U. Deva; Jana, Anukul
Abstract : Herein we report the synthesis of an N-heterocyclic carbene (NHC)-stabilised phosphinidene oxide, by the controlled oxygenation of a phosphinidene under ambient conditions. Abstract : Here we report the synthesis of an N-heterocyclic carbene (NHC)-stabilised phosphinidene oxide by the controlled oxygenation of a phosphinidene under ambient conditions. This compound can be further oxygenated to a phosphinidene dioxide. The stoichiometric reduction of a phosphinidene oxide with KC8 resembles the pinacol coupling reaction–the reduction of a carbonyl compound. We also looked at the stoichiometric oxidation of NHC-coordinated phosphinidene, phosphinidene oxide and phosphinidene dioxide with [NO][SbF6 ].